1997
DOI: 10.1128/aac.41.4.812
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of copper-mediated inactivation of herpes simplex virus

Abstract: The inactivation of herpes simplex virus (HSV) by copper was enhanced by the following reducing agents at the indicated relative level: ascorbic acid > hydrogen peroxide > cysteine. Treatment of HSV-infected cells with combinations of Cu(II) and ascorbate completely inhibited virus plaque formation to below 0.006% of the infectious virus input, while it maintained 30% viability for the host mammalian cells. The logarithm of the surviving fraction of HSV mediated by 1 mg of Cu(II) per liter and 100 mg of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
47
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 25 publications
7
47
0
2
Order By: Relevance
“…These results indicate that copper ions leached from Cu 2 O were not a major contributor to the antiviral activity. Sagripanti et al showed that 50% of herpes simplex viruses (HSVs) still survived after treatment with 10 ppm of Cu 2+ ions, which may support our present results [3].…”
Section: Investigation Of the Origin Of Antiviral Activities Of Cuprosupporting
confidence: 92%
See 2 more Smart Citations
“…These results indicate that copper ions leached from Cu 2 O were not a major contributor to the antiviral activity. Sagripanti et al showed that 50% of herpes simplex viruses (HSVs) still survived after treatment with 10 ppm of Cu 2+ ions, which may support our present results [3].…”
Section: Investigation Of the Origin Of Antiviral Activities Of Cuprosupporting
confidence: 92%
“…Films and fabrics coated with these inorganic powders are often used as antibacterial and antiviral materials. In copper case, many studies have demonstrated the high antimicrobial activity of copper ions [3], metals and alloys [4][5][6], and oxides [7][8][9][10]. However, no systematic study has been done in solid state copper compounds discriminating their oxidation states.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cu-NTA, at the same concentration creates more DNA damages and to rectify those damages, recombinant repair mechanism and SOS repair mechanism are to be operative. Parallel to our observations, earlier researchers reported genotoxic potential of Cu in different microbial systems [43,44]. Although the precise mechanism of Cuinduced genotoxicity is not yet established, intriguing observations propose that DNA damage is an important component of Cu-toxicity facilitated through Fenton like process [41,45].…”
Section: Genotoxicity Studysupporting
confidence: 69%
“…Copper appears to exert its killing effect by binding to DNA causing single strand breaks and base modification. This effect is enhanced by hydrogen peroxide and free radicals are believed to be involved in the reaction [20][21][22].…”
Section: Introductionmentioning
confidence: 97%